AB0999 Detection of calcium crystals in knee osteoarthritis synovial fluid. A comparison between ordinary light and scanning electronic microscopy. (23rd January 2014) - Frallonardo, P.; Ramonda, R.; Oliviero, F.; Campana, C.; Modesti, V.; Lorenzin, M.; Peruzzo, L.; Punzi, L.
Abstract : Background: Osteoarthritis (OA) is the most common joint disease and the knee is frequently involved. OA is characterized by a progressive loss of articular cartilage, osteophyte formation, thickening of the subchondral bone, but as well as some signs of intraarticular inflammation with synovitis. Multiple factors such as mechanical factors, genetics and aging are involved in the pathogenesis of OA. However there is still some debate about the role of inflammation in pathogenetic mechanisms of OA (1). Only a few studies have recently recognized the potential role of calcium crystals (CC) in synovial inflammation and in OA progression (2-4). The most common CC in OA are calcium pyrophosphate dihydrate (CPP) and basic calcium phosphate (BCP), including hydroxyapatite, octacalcium and tricalcium phosphate. Several studies demonstrated that CC occur in up to 60% of SF in OA patients. Although it is difficult to identify CC in SF of OA, the relationship between pathogenetic mechanisms or disease progression and the presence of CC is very interesting. Recognition of CPP, which range in length from 2-20 μm, is a relatively simple procedure. Nevertheless they are not always released in a uniform manner and it is not simple to detect them even when the most sensitive methods are been used in. Due to their sub-microscopic size BCP (70-250 Å) detection is particularly difficult. Objectives: The aim of the study was to identify CC in SF of OA patients through compensated polarized light microscopy (CPML) and alizarin red S staining (AS), and by ultrasensitive analysis with scanning electronic microscopy (SEM), to detect whatever concordance exists between them. Methods: We analyzed the SF74 patients with knee osteothritis (KOA) (48 F, mean age 64.85±9.33, range 50-89 yrs) by CPML, AS and by SEM. The concordance between CPML and SEM was evaluated by Cohen's kappa coefficient Results: CPP crystals were found in 28.4% by CPML and in 32.4% by SEM. BCP crystals were suspected in 32.4% of the samples that were positive according to AS, while they we found by SEM in 10.8% of SF. By according to kappa coefficient, the concordance between CPML and SEM was 0.78% for CPP and 0.69% for BCP. CPP and BCP were simultaneously positive in 26% of the samples by SEM. Conclusions: CPML and AS are tecniques routinely used to detect CC in SF of OA patients. However use of a highly sensitive method such as SEM, ensures accurate detection of CC and this could help to clarify the its potential role in pathogenetic mechanisms and in progression of OA. References: AK Rosenthal. Crystls, inflammation, and osteothritis 2011;Curr Opin Rheumatol 23:170-3 S Nalbant, JAM Martinez, T Kitumnuaypong, G Clayburnet, M Sieck and HR Jr. Synovial fluid features and their relations to osteothritis severity: new findings from sequential atudies. Osteoarthritis and Cartilage 2003;11:54-4 GM McCarthy, HS Cheung. Point: Hydroxyapatite crystal deposition is intimately involved in the pathogenesis and progression of human osteoarthritis. Curr Rheumatol Rep. 2009;11:141-7. YZ Liu, AP Jackson and SD Cosgrove. Contribution of calcium-containing crystals to cartilage degradation and synovial inflammation in osteothritis. Osteoarthritis and Cartilage 2009;17:1333-40 Disclosure of Interest: None Declared